Preparation and Evaluation of Cyproterone Acetate LiposomeforTopical Drug Delivery: Cyproterone acetate liposome for topical drug delivery - Soleiman Mohammadi-Samani,; Hashem Montaseri,; Minoo Jamshidnejad, (Iranian Journal of Pharmaceutical Sciences, 2009)
Cyproterone acetate (CA) has been loaded to liposome by solvent evaporation and thin film formation technique. The effects of some formulation variables such as temperature of organic solvent evaporation, rotary evaporator speed, volume of organic solvent, volume of balloon and temperature of hydrating buffer has been evaluated. The data showed that bigger balloon with higher surface area has better capacity for lipidic film formation; also the best temperature for solvent evaporation and film hydration was 40 °C. According to the data with higher drug/lipid ratio,it is possible to load higher amount of drug into liposome but optimum loading could be obtained at phosphatidylcholine (PC): cholesterol/drug ratio of 1:2:0.5 (with maximum 74±6.11% loading efficiency). Finally percutaneous absorption of CA from simple gel and liposomal formulations was assessed. The results showed that liposomal formulation has better penetration potential than conventional CAformulation (simple gel).